Analisa Fenomena Springback Tailor Welded Blank (TWB) Stainless - Besi Pada Proses U - Bending - Mustahfirin, Mustahfirin (2016)
Tailored welded blanks is a combination of two or more kinds of metal sheet with a thickness (thickness) is different or the same which are connected with the use of welding In welding there are several methods including SMAW therefore of interest in this study to examine the effect of variations in materials, the phenomenon of spring back Using U-bending test. This research method early stages of welding connection with AWS standards. Furthermore, using a tensile testing standard ASTM E-8. Testing springback using a die tool set, while to know the big spring backnya using paper mili meter block by way of a mall. From the test results obtained difference values of each of the materials used for the value of the tensile strength of the specimen, the highest elasticity modulus value on the variation of ferrous materials - iron amounted to 40 000 MPa, with a greatest springback -1 mm to the right side and -2 mm to the side left, while for variations in steel material - steel amounted to 55555.55 MPa, with a large spring back to -3 mm -2 mm and a right side to the left side, and a variety of stainless materials - iron at 44285.71 MPa, with a large spring back - 1.5 mm, on the right side and -3 mm to the left side.